Ketersediaan Ruang Terbuka Hijau di Kelurahan Lembo Kota Makassar - Paraswatih Paraswatih; Nursyam AS; Fadhil Surur (ARSITEKTURA, 2020)
Green open space in Makassar City was decreasing due to population growth and high land demand. The phenomenon that occured was that land use as a green open space was decreasing due to an increase in built space. This study aimed to determine the availability of green open space in the Lembo Village, Tallo District, Makassar. Qualitative descriptive analysis and superimpose analysis were used to determine the availability of green open space in that area. The results showed that public and private green open spaces were available in that area with an area of 18.12 Ha or equivalent to 33.56% of the total area. The green open space was at least 30% of the total area, this condition shows sustainability.